BIOMARKERS IN MEDICINE - PINAR, ATUKEREN; HAFIZE, UZUN (BENTHAM SCIENCE PUBLISHER, 2022)
Biomarkers in Medicine is a comprehensive guide to understanding the current and future status of biomarkers. The book features 27 chapters focusing on disease biomarkers for diseases such as cancer, neurodegenerative diseases, cardiac diseases, metabolic conditions and much more. This book supplies readers with the unique insight of experts in multiple specialties in medicine and life sciences who have extensive experience in diagnostics and clinical laboratories. The book includes case studies and practical examples from different classes of biomarkers on different platforms, including new data for biomarkers in different therapeutic indications. In addition to presenting biomarker information, each chapter covers the relevant pathology and also emphasizes on preclinical and clinical manifestation of the disease process. Clinicians managing patients or clinical trials, clinical researchers, clinical laboratories, diagnostic companies, regulatory agencies, medical school graduate students, academic students, and the general public involved in healthcare delivery will all benefit from information presented in this book.